Problematika Kompetensi Guru PAI dalam Implementasi Kurikulum 2013 (Studi Kasus di MA Arraudlah Tumapel Gresik) - Ali Ahmad Yenuri (Kuttab : Jurnal Ilmu Pendidikan Islam, 2019)
The 2013 curriculum, apart from emphasizing character education, also adopts scientific lecturers in the learning process. Since the implementation of this curriculum has become a national policy until now, there are still many teachers who have not been able to implement the ideal standard in the education process in Indonesia. Taking the case at MA Ar-Raudlah, Tumapel, and Gresik, this study aims to reveal the problems teachers face in implementing K-13 in their educational institutions. This type of research includes qualitative research with a case study approach. This study concluded that teachers at MA Ar-raudlah Tumapel Gresik had problems implementing the 2013 curriculum, namely those related to pedagogy, professional, and social competency problems. In the pedagogical competence of teachers, it is found that it is still challenging to design and evaluate learning. As for the professional competence issues related to the lack of time in preparing teaching materials, and at the same time, minimal mastery in operationalizing technology. Then the problem of social competence is related to lack of interaction with students and teacher peers in educational institutions.